Hubungan Kualitas Tidur dengan Fungsi Kognitif Lansia Di Panti Sosial - Desy Ria Simanjuntak; I Gusti Ayu Devia Satyavati (Pro-Life, 2023)
Decreased physiological function causes the elderly to experience sleep disturbances caused by a decrease in the hormone melatonin with increasing age. Disruption of sleep duration has an impact on decreasing cognitive function, will affect daily activities, so that it can reduce the quality of life of the elderly. This study aims to analyze the relationship between sleep quality and cognitive function in the elderly. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) and cognitive function using the Mini Mental Status Examination (MMSE). The design of this research is observational analytic with a sample of 60 respondents. The results showed that 65% of the elderly with poor sleep quality, 45% mild cognitive function decline, and 25% severe cognitive function decline. Based on the chi-square test, it shows that there is a significant relationship between sleep quality and cognitive function in the elderly with p value = 0.013. Keywords: Sleep quality, cognitive, eldery